Inovasi Media Pembelajaran Berbasis Literasi Ekologi untuk Mengembangkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Noviyanti Noviyanti; Yeri Sutopo; Agus Yuwono (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This study aims to develop teaching materials in the form of picture storybooks based on ecological literacy to improve critical thinking skills of elementary school students. The development model used is ADDIE (Analysis, Design, Development, Implementation, Evaluation). This research is motivated by the lack of innovative learning media that can connect ecological issues with Natural and Social Sciences (IPAS) learning. The research subjects were 50 fifth-grade students at Al Ikhlas Islamic Elementary School who were divided into an experimental group and a control group. The validation process involved five media experts and five material experts, while the practicality test involved 15 teachers and 25 students. The validation results showed that the picture storybook obtained the "Very Appropriate" category with an average score of 4.61 in the media aspect and 4.43 in the material aspect. The practicality test also showed a positive response with a practicality level of 86.43% which is included in the "Practical" category. In terms of effectiveness, the results of the N-Gain analysis showed an increase in critical thinking skills of 23.10% in the experimental group, much higher than the control group which only increased by 6.08%. Although this increase is categorized as "Low," it is statistically significant. This is demonstrated by a t-test with a significance value of 0.002 < 0.05, indicating a significant difference between the two groups. This research makes an important contribution to elementary education, particularly in providing contextual learning media that are not only engaging but also foster environmental awareness. By integrating ecological literacy into picture storybooks, students gain a more meaningful learning experience and are trained to develop critical thinking skills. These findings confirm that media based on environmental contexts can be an innovative alternative to support a more effective learning process.